Dry and comfortable antibacterial menstrual period trousers and preparation method thereof
Through the combination of ultra-microcapsule-like inclusion complex formed by β-cyclodextrin and matrine and macroporous superwater-absorbent resin, the existing silver-loading antibacterial fiber nanosilver shedding and toxicity problems are solved, and the long-term antibacterial, diversion and breathability of dry and antibacterial menstrual pants are achieved.
Patent Information
- Application Number
- CN202411661897.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silver-loaded antibacterial fibers are prone to falling off during use, and have poor antibacterial effects. In addition, the silver ions and other components have certain toxicity, which may cause potential harm to the female vagina.
The ultra-microcapsule-like inclusion compound is formed by β-cyclodextrin and matrine, which is adsorbed on the surface of the macroporous superwater-absorbing resin to form an antibacterial composite resin powder, and sprayed on the surface of the composite aerogel sheet to accurately control the release of matrine to avoid interference with the normal bacteria in the female private parts.
It achieves long-term antibacterial, rapid diversion and improves the rebound strength of menstrual pants, while effectively preventing heat transfer, increasing breathability, and maintaining the balance of female vaginal bacteria.
Smart Images

Figure BDA0005143627490000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of female sanitary products, and in particular relates to a dry antibacterial menstrual pants and a preparation method thereof. Background Art
[0002] Menstrual blood is a mixture of blood and some shed endometrium, cervical mucus and vaginal secretions. Menstrual blood is dark in color, slightly sticky, and not easy to coagulate into blood clots. If you look closely, you will see small and thin fragments, sometimes blood clots, or black blood. Due to the accumulation of blood in the vagina, its normal acidity is reduced, and the small cervical opening is in an open state, which weakens the natural shielding effect of the vagina and cervix against bacterial infection. The wounds caused by the shedding of the endometrium also reduce the ability of the uterine cavity to resist infection. If you do not pay attention to menstrual care, it will cause menstrual disorders or other gynecological diseases.
[0003] Chinese patent application CN113274197A discloses a menstrual pants, wherein an antibacterial layer is arranged in the surface layer, and the antibacterial layer contains at least one of silver ions, organic guanidines and quaternary ammonium salts. The antibacterial layer arranged in the surface layer can effectively kill microorganisms, avoid bacterial growth, prevent odor generation, and protect women's health. Although this silver-loaded antibacterial fiber can be antibacterial, the nanosilver attached to the surface of the antibacterial fiber is physically adsorbed. When the antibacterial surface layer is prepared by using this type of silver-loaded antibacterial fiber, the nanosilver is easy to fall off the fiber, and the antibacterial effect is poor. In addition, silver ions, organic guanidines and quaternary ammonium salts have certain toxicity and may cause potential harm to the vagina. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing dry antibacterial menstrual pants, using β-cyclodextrin and matrine to form an ultra-microcapsular inclusion complex, which is adsorbed on the surface of a macroporous superabsorbent resin to form an antibacterial composite resin powder, which is sprayed on the surface of a composite aerogel sheet. When encountering blood, the binding force between β-cyclodextrin and matrine is weakened, and matrine is released. This design aims to accurately control the release of matrine, thereby avoiding unnecessary interference with the normal flora of women's private parts.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A dry antibacterial menstrual pants is prepared by the following steps:
[0007] The hydrophilic nonwoven fabric as the surface layer, the antibacterial sandwich layer, the hot air nonwoven fabric as the guide layer, the nonwoven fabric as the absorbent core layer wrapped with a mixed material of fluff pulp and super absorbent resin, and the PP breathable microporous film as the base film are cut and formed respectively, overlapped in sequence, and bonded by hot melt adhesive to obtain the crotch part of the trouser body, and the crotch part and the waist part of the trouser body are bonded by hot melt adhesive to obtain the dry antibacterial menstrual pants.
[0008] The antibacterial sandwich layer is prepared by the following steps:
[0009] Step 1: dissolving matrine in anhydrous ethanol to obtain a matrine solution with a mass fraction of 50-60%; adding β-cyclodextrin and deionized water into a reaction kettle, stirring for 10-15 minutes at 60-70° C. and 200-300 r / min to obtain a β-cyclodextrin solution with a mass fraction of 70-75%;
[0010] A matrine solution with a mass fraction of 50-60% is added to a reactor containing a β-cyclodextrin solution with a mass fraction of 70-75%, and ultrasonic dispersion is performed for 40-60 minutes. The stirring is continued for 2-3 hours. Anhydrous ethanol is added to the reactor and stirred for 20-30 minutes. The mixture is cooled and crystallized at 0-4°C for 8-12 hours. The mixture is filtered and the filter cake is washed 2-3 times with an ethanol solution with a volume fraction of 30-35% to remove the residual matrine in the filter cake. The mixture is vacuum dried at 60-80°C for 1-2 hours to obtain a nano antibacterial inclusion compound powder.
[0011] Step 2: Add styrene, divinylbenzene, isooctane as a porogen, benzoyl peroxide as an initiator, polyvinyl alcohol as a dispersant and deionized water into a reactor, stir for 20-30 minutes at 60-70°C and 400-500r / min, add absorbent resin powder into the reactor for swelling, continue stirring and reacting for 4-6 hours, filter, wash the filter cake with deionized water at 80-85°C for 4-5 times, dry at 60-80°C in vacuum to constant weight, crush, and pass through a 180-200 mesh sieve to obtain macroporous super absorbent resin powder; mix the macroporous super absorbent resin powder and the nano antibacterial inclusion compound powder in a mass ratio of 2:1 to obtain an antibacterial composite resin powder.
[0012] Step 3: Add glacial acetic acid and anhydrous ethanol to the reactor, ultrasonically disperse for 40-60 minutes, stir for 30-45 minutes at 20-25°C and 200-300r / min, add 70-75% mass fraction of tetrabutyl titanate solution, bagasse fiber suspension, nano zeolite and deionized water to the reactor, ultrasonically disperse for 40-60 minutes, stir for 20-30 minutes at 20-25°C and 200-300r / min, then pour the obtained mixture into a mold and freeze it with liquid nitrogen for 10-12 minutes, then place it in a freeze dryer for freeze drying for 48-50 hours, cut and shape to obtain a 1-2mm composite aerogel sheet, and add the antibacterial composite resin powder at 0.1-0.2g / cm 2 The spraying amount is evenly sprayed on the surface of the composite aerogel sheet to obtain an antibacterial sandwich layer.
[0013] Furthermore, in step 1, the usage ratio of matrine solution, β-cyclodextrin solution and anhydrous ethanol is 200-250mL: 300-350mL: 300-310mL.
[0014] Furthermore, in step 2, the dosage ratio of styrene, divinylbenzene, isooctane, benzoyl peroxide, polyvinyl alcohol, deionized water and water-absorbing resin powder is 90-100 g: 300-350 mL: 110-120 g: 10-12 g: 6-8 g: 550-600 mL: 200-210 g.
[0015] Furthermore, in step three, the freeze-drying temperature is -96.5°C and the pressure is 13.0-14.0Pa.
[0016] Furthermore, in step three, the dosage ratio of glacial acetic acid, anhydrous ethanol, tetrabutyl titanate solution, bagasse fiber suspension, nano zeolite and ion water is 50-80g: 220-250mL: 50-60mL: 100-120mL: 100-120g: 400-450mL.
[0017] Further, the water-absorbent resin powder is prepared by the following steps:
[0018] Starch and deionized water are added to a reaction kettle, heated to 90-100° C. under nitrogen protection, gelatinization reaction is carried out for 30-40 minutes, and cooled to 55-65° C., acrylic acid solution with a neutralization degree of 45-55% and N,N'-methylenebisacrylamide as a cross-linking agent are added to the reaction kettle, and ammonium sulfate solution as an initiator is added dropwise at a speed of 30-40 drops / min under nitrogen protection. After the addition is completed, stirring is carried out at 60-70° C. and 200-300 r / min for 3-4 hours, filtering, washing the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum drying at 60-80° C. for 1-2 hours, crushing, and passing through a 100-120 mesh sieve to obtain a water-absorbing resin powder.
[0019] Furthermore, the concentration of acrylic acid in the acrylic acid solution with a neutralization degree of 45-55% is 5-6 mol / L.
[0020] Furthermore, the usage ratio of starch, deionized water, acrylic acid solution, N,N'-methylenebisacrylamide and ammonium sulfate solution is 180-200 g: 500-600 mL: 100-120 mL: 120-130 g: 120-130 mL.
[0021] Further, the bagasse fiber suspension is prepared by the following steps:
[0022] After the bagasse is deflated by a pulp defragmenter, it is soaked in deionized water for 12-15 hours and ground at a grinding speed of 1500-1600 r / pm for 5-6 cycles, each cycle lasting 30-40 minutes, to obtain a bagasse fiber suspension with a solid content of 4-5wt%.
[0023] Beneficial effects of the present invention:
[0024] 1. The present invention prepares a dry antibacterial menstrual pants, wherein the antibacterial sandwich layer has the functions of long-lasting antibacterial, rapid fluid conduction and improving the resilience of the menstrual pants, and can effectively prevent heat transfer and increase air permeability.
[0025] β-cyclodextrin embeds matrine into its annular cavity through van der Waals force to form an ultra-microcapsular nano-antibacterial inclusion powder. In a dry state, the matrine in the inclusion powder has a strong binding force with β-cyclodextrin, allowing matrine to be stably preserved. It does not have antibacterial properties under normal conditions. When it encounters blood, the affinity of water molecules for the external hydroxyl groups of cyclodextrin is enhanced, resulting in a weakened binding force between matrine and β-cyclodextrin, thereby releasing matrine, thereby effectively avoiding the impact on the female private flora and maintaining the balance of the female vaginal flora.
[0026] 2. The antibacterial composite resin powder prepared by the present invention is an interpenetrating polymer network with a macroporous structure and high water absorption performance. The antibacterial composite resin powder has excellent load capacity, can evenly distribute and carry more nano antibacterial inclusion compounds, and quickly absorbs water and swells when encountering liquids such as blood. This process will compress and promote the release of the nano antibacterial inclusion compounds loaded on the surface, thereby accelerating the release of matrine contained therein, achieving a rapid and targeted antibacterial effect; the antibacterial composite resin powder has a macroporous structure, and matrine is tightly adsorbed on the surface through the action of van der Waals force, thereby achieving a long-lasting antibacterial effect.
[0027] 3. The antibacterial sandwich layer prepared by the present invention is obtained by spraying antibacterial composite resin powder on the surface of the composite aerogel sheet. The composite aerogel sheet prepared by using titanium dioxide, bagasse fiber and zeolite as raw materials is helpful to improve the problem that the intermolecular force of traditional aerogel is weak, resulting in relatively low mechanical strength and high brittleness; because it has an extremely high specific surface area, nanoscale pore structure and extremely low thermal conductivity, it can effectively prevent heat transfer, increase air permeability, and help improve the stuffiness caused by wearing menstrual pants for a long time. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1: A dry antibacterial menstrual pants, comprising the following steps:
[0030] S1: dissolving matrine in anhydrous ethanol to obtain a matrine solution with a mass fraction of 50%; adding β-cyclodextrin and deionized water into a reaction kettle, stirring at 60° C. and 200 r / min for 10 min, to obtain a β-cyclodextrin solution with a mass fraction of 70%;
[0031] Add 200 mL of 50% matrine solution into a reactor containing 300 mL of 70% β-cyclodextrin solution, perform ultrasonic dispersion for 40 min, continue stirring for 2 h, add 300 mL of anhydrous ethanol into the reactor and stir for 20 min, cool and crystallize at 0°C for 8 h, filter, wash the filter cake twice with 30% ethanol solution by volume to remove residual matrine in the filter cake, and dry under vacuum at 60°C for 1 h to obtain a nano antibacterial inclusion compound powder.
[0032] S2: 180g starch and 500mL deionized water were added to a reactor, heated to 90°C under nitrogen protection, gelatinized for 30min, cooled to 55°C, and added with 100mL 5mol / L acrylic acid solution with a neutralization degree of 45% and 120g N,N'-methylenebisacrylamide as a cross-linking agent in an ice bath at 0°C. Under nitrogen protection, 120mL ammonium sulfate solution as an initiator was added dropwise at a rate of 30 drops / min. After the addition was completed, it was stirred at 60°C and 200r / min for 3h, filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, dried under vacuum at 60°C for 1h, crushed, and passed through a 100-mesh sieve to obtain a water-absorbent resin powder.
[0033] S3: Add 90g of styrene, 300mL of divinylbenzene, 110g of isooctane as a porogen, 10g of benzoyl peroxide as an initiator, 6g of polyvinyl alcohol as a dispersant and 550mL of deionized water into a reactor, stir at 60°C and 400r / min for 20min, add 200g of absorbent resin powder into the reactor for swelling, continue stirring and reacting for 4h, filter, wash the filter cake with 80°C deionized water for 4 times, vacuum dry at 60°C to constant weight, crush, and pass through a 180-mesh sieve to obtain macroporous super absorbent resin powder; mix the macroporous super absorbent resin powder and nano antibacterial inclusion compound powder in a mass ratio of 2:1 to obtain antibacterial composite resin powder.
[0034] S4: After the bagasse is defragmented by a pulp defragmenter, it is soaked in deionized water for 12 hours and ground at a grinding speed of 1500 r / pm for 5 cycles, each cycle lasting 30 minutes, to obtain a bagasse fiber suspension with a solid content of 4 wt%.
[0035] S5: Add 50g of glacial acetic acid and 220mL of anhydrous ethanol to the reactor, ultrasonically disperse for 40min, stir for 30min at 20℃ and 200r / min, add 50mL of 70% tetrabutyl titanate solution, 100mL of bagasse fiber suspension, 100g of nano zeolite and 400mL of deionized water to the reactor, ultrasonically disperse for 40min, stir for 20min at 20℃ and 200r / min, then pour the obtained mixture into a mold and freeze it with liquid nitrogen for 10min, then place it in a freeze dryer, freeze-dry at -96.5℃ for 48h, pressure of 13.0Pa, cut into shape, and obtain a 1mm composite aerogel sheet, and the antibacterial composite resin powder is granulated at 0.1g / cm 2 The spraying amount is evenly sprayed on the surface of the composite aerogel sheet to obtain an antibacterial sandwich layer.
[0036] S6: Cut and shape the hydrophilic nonwoven fabric as the surface layer, the antibacterial sandwich layer, the hot air nonwoven fabric as the guide layer, the nonwoven fabric as the absorbent core layer wrapped with a mixed material of fluff pulp and super absorbent resin, and the PP breathable microporous film as the base film, overlap them in sequence, and bond them with hot melt adhesive to obtain the crotch part of the trouser body. Bond the crotch part and the waist part of the trouser body with hot melt adhesive to obtain the dry antibacterial menstrual pants.
[0037] Embodiment 2: A dry antibacterial menstrual pants, comprising the following steps:
[0038] S1: dissolving matrine in anhydrous ethanol to obtain a matrine solution with a mass fraction of 55%; adding β-cyclodextrin and deionized water into a reactor, stirring at 65°C and 250r / min for 13min, to obtain a β-cyclodextrin solution with a mass fraction of 73%;
[0039] Add 225 mL of 55% matrine solution into a reactor containing 300 mL of 70% β-cyclodextrin solution, ultrasonically disperse for 50 min, continue stirring for 2.5 h, add 300 mL of anhydrous ethanol into the reactor and stir for 25 min, cool and crystallize at 3°C for 10 h, filter, wash the filter cake three times with 33% ethanol solution by volume to remove residual matrine in the filter cake, and vacuum dry at 75°C for 1.5 h to obtain a nano antibacterial inclusion complex powder.
[0040] S2: 190g starch and 550mL deionized water were added to a reactor, heated to 95°C under nitrogen protection, gelatinized for 35min, cooled to 60°C, and added with 110mL 6mol / L acrylic acid solution with a neutralization degree of 50% and 125g N,N'-methylenebisacrylamide as a cross-linking agent in a 3°C ice bath. Under nitrogen protection, 125mL ammonium sulfate solution as an initiator was added dropwise at a rate of 35 drops / min. After the addition was completed, it was stirred at 65°C and 250r / min for 3.5h, filtered, and the filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively, dried in vacuo at 75°C for 1.5h, crushed, and passed through a 110-mesh sieve to obtain a water-absorbent resin powder.
[0041] S3: Add 95g of styrene, 320mL of divinylbenzene, 115g of isooctane as a porogen, 11g of benzoyl peroxide as an initiator, 7g of polyvinyl alcohol as a dispersant and 580mL of deionized water into a reactor, stir at 65°C and 450r / min for 25min, add 205g of absorbent resin powder into the reactor for swelling, continue stirring and reacting for 5h, filter, wash the filter cake with 83°C deionized water for 5 times, dry under vacuum at 70°C to constant weight, crush, and pass through a 190-mesh sieve to obtain macroporous super absorbent resin powder; mix the macroporous super absorbent resin powder and nano antibacterial inclusion compound powder in a mass ratio of 2:1 to obtain antibacterial composite resin powder.
[0042] S4: After the bagasse is defragmented by a pulp defragmenter, it is soaked in deionized water for 14 hours and ground at a grinding speed of 1500 / pm for 6 cycles, each cycle lasting 35 minutes, to obtain a bagasse fiber suspension with a solid content of 5 wt%.
[0043] S5: 70g of glacial acetic acid and 230mL of anhydrous ethanol were added to the reactor, ultrasonically dispersed for 50min, stirred at 23℃ and 250r / min for 40min, 55mL of 73% tetrabutyl titanate solution, 110mL of bagasse fiber suspension, 110g of nano zeolite and 430mL of deionized water were added to the reactor, ultrasonically dispersed for 50min, stirred at 23℃ and 250r / min for 25min, and then the obtained mixture was poured into a mold and frozen with liquid nitrogen for 11min, and then placed in a freeze dryer, freeze-dried at -96.5℃ for 49h, and the pressure was 14.0Pa, cut into pieces, and a 1.5mm composite aerogel sheet was obtained. The antibacterial composite resin powder was granulated at 0.15g / cm 2 The spraying amount is evenly sprayed on the surface of the composite aerogel sheet to obtain an antibacterial sandwich layer.
[0044] S6: Cut and shape the hydrophilic nonwoven fabric as the surface layer, the antibacterial sandwich layer, the hot air nonwoven fabric as the guide layer, the nonwoven fabric as the absorbent core layer wrapped with a mixed material of fluff pulp and super absorbent resin, and the PP breathable microporous film as the base film, overlap them in sequence, and bond them with hot melt adhesive to obtain the crotch part of the trouser body. Bond the crotch part and the waist part of the trouser body with hot melt adhesive to obtain the dry antibacterial menstrual pants.
[0045] Embodiment 3: A dry antibacterial menstrual pants, comprising the following steps:
[0046] S1: dissolving matrine in anhydrous ethanol to obtain a matrine solution with a mass fraction of 60%; adding β-cyclodextrin and deionized water into a reaction kettle, stirring at 70° C. and 300 r / min for 15 min, to obtain a β-cyclodextrin solution with a mass fraction of 75%;
[0047] Add 250 mL of 60% matrine solution into a reactor containing 350 mL of 75% β-cyclodextrin solution, ultrasonically disperse for 60 minutes, continue stirring for 3 hours, add 310 mL of anhydrous ethanol into the reactor and stir for 30 minutes, cool and crystallize at 4°C for 12 hours, filter, wash the filter cake three times with 35% ethanol solution by volume to remove residual matrine in the filter cake, and vacuum dry at 80°C for 2 hours to obtain nano antibacterial inclusion complex powder.
[0048] S2: 200g starch and 600mL deionized water were added to a reactor, heated to 100°C under nitrogen protection, gelatinized for 40min, cooled to 65°C, and added with 120mL 6mol / L acrylic acid solution with a neutralization degree of 55% and 130g N,N'-methylenebisacrylamide as a cross-linking agent in an ice bath at 4°C. Under nitrogen protection, 130mL ammonium sulfate solution as an initiator was added dropwise at a rate of 40 drops / min. After the addition was completed, it was stirred at 70°C and 300r / min for 4h, filtered, and the filter cake was washed 3 times with deionized water and anhydrous ethanol respectively, dried in a vacuum at 80°C for 2h, crushed, and passed through a 120-mesh sieve to obtain a water-absorbent resin powder.
[0049] S3: Add 100g styrene, 350mL divinylbenzene, 120g isooctane as a porogen, 12g benzoyl peroxide as an initiator, 8g polyvinyl alcohol as a dispersant and 600mL deionized water into a reactor, stir at 70°C and 500r / min for 30min, add 210g absorbent resin powder into the reactor for swelling, continue stirring and reacting for 6h, filter, wash the filter cake with 85°C deionized water for 5 times, vacuum dry at 80°C to constant weight, crush, and pass through a 200-mesh sieve to obtain a macroporous super absorbent resin powder; mix the macroporous super absorbent resin powder and the nano antibacterial inclusion compound powder in a mass ratio of 2:1 to obtain an antibacterial composite resin powder.
[0050] S4: After the bagasse is defragmented by a pulp defragmenter, it is soaked in deionized water for 15 hours and ground at a grinding speed of 1600 r / pm for 6 cycles, each cycle lasting 40 minutes, to obtain a bagasse fiber suspension with a solid content of 5 wt%.
[0051] S5: 80g of glacial acetic acid and 250mL of anhydrous ethanol were added to the reactor, ultrasonically dispersed for 60min, stirred at 25℃ and 300r / min for 45min, 60mL of 75% tetrabutyl titanate solution, 120mL of bagasse fiber suspension, 120g of nano zeolite and 450mL of deionized water were added to the reactor, ultrasonically dispersed for 60min, stirred at 25℃ and 300r / min for 30min, and then the obtained mixture was poured into a mold and frozen with liquid nitrogen for 12min, and then placed in a freeze dryer, freeze-dried at -96.5℃ for 50h, and the pressure was 14.0Pa, cut into pieces, and a 2mm composite aerogel sheet was obtained. The antibacterial composite resin powder was granulated at 0.2g / cm 2 The spraying amount is evenly sprayed on the surface of the composite aerogel sheet to obtain an antibacterial sandwich layer.
[0052] S6: Cut and shape the hydrophilic nonwoven fabric as the surface layer, the antibacterial sandwich layer, the hot air nonwoven fabric as the guide layer, the nonwoven fabric as the absorbent core layer wrapped with a mixed material of fluff pulp and super absorbent resin, and the PP breathable microporous film as the base film, overlap them in sequence, and bond them with hot melt adhesive to obtain the crotch part of the trouser body. Bond the crotch part and the waist part of the trouser body with hot melt adhesive to obtain the dry antibacterial menstrual pants.
[0053] Comparative Example 1: The nano antibacterial inclusion compound powder was prepared by the method of step S1 in Example 3, except that the nano silver powder was used.
[0054] Comparative Example 2: By the method of step S3 in Example 3, the macroporous super absorbent resin powder is replaced with a super absorbent resin and mixed evenly with the nano antibacterial inclusion compound powder to obtain an antibacterial composite resin powder.
[0055] Comparative Example 3: The method of step S5 in Example 3 was used without adding nano zeolite.
[0056] Styrene, divinylbenzene, isooctane, polyvinyl alcohol, tetrabutyl titanate, acrylic acid, N,N'-methylenebisacrylamide and ammonium sulfate in the examples and comparative examples were purchased from Sigma-Aldrich.
[0057] Benzoyl peroxide was purchased from Dongying Haijing Chemical Co., Ltd.
[0058] Starch was purchased from Shanghai Darui Fine Chemicals Co., Ltd.
[0059] The hydrophilic nonwoven fabric, hot air nonwoven fabric, nonwoven fabric wrapped with a mixed material of fluff pulp and a highly absorbent resin, and PP breathable microporous film in the examples and comparative examples are all purchased from commercial products.
[0060] The performance of the antibacterial sandwich layers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:
[0061] 1. Antibacterial rate test: Take 100 mL of Staphylococcus aureus suspension with a concentration of 5.6×105 cfu / mL, and evenly spread it on the surface of a culture dish with a diameter of 95 mm containing nutrient agar. The antibacterial sandwich layer is divided into two groups. The first group is not water-permeable, and the second group is fixed at both ends on the hollow base in the middle. Deionized water is flushed at a speed of 0.9 m / s for 10 minutes at a vertical position above the base. The two groups are respectively attached to the above-mentioned culture dishes in a sterile state, and cultured in a constant temperature incubator at 37°C for 24 hours. The diameter (mm) of the inhibition zone around the sample material is measured with a vernier caliper.
[0062] 2. Water absorption rate: Refer to GB / T28004.2-2021 "Diaper Absorption Rate Test Method", place the menstrual pants on a curved sample base covered with absorbent paper, ensure that the absorption area is completely aligned with the standard test liquid adding module, and inject 300mL of normal saline into the liquid adding module through the liquid adding device. At the same time, start the automatic timer to record the time required for the menstrual pants to completely absorb the normal saline from the start of liquid addition. Perform three liquid adding operations each time, and use the average of the three absorption times (s) to indicate the water absorption rate of the sample. The shorter the absorption time, the faster the water absorption rate.
[0063] 3. Air permeability test: Refer to GB / T5453-1997 "Test method for air permeability of textile fabrics" and use a fabric air permeability meter to test the air permeability R (mm / s) of menstrual pants. The test area is 5cm 2 , sample pressure difference is 100Pa.
[0064] 4. Resilience test: Cut the antibacterial sandwich layer into a 5cm wide and 10cm long elastic material as the test section, place a 20g weight on the test section to simulate the pressure when worn, take the current thickness as the base point, keep it for 10s, remove the weight, and record the thickness (mm) of the test section. The higher the thickness, the better the resilience. Repeat the data recording 3 times and take the average value of the results.
[0065] Table 1
[0066]
[0067] As can be seen from Table 1, the antibacterial rate in Example 1-Example 3 is significantly better than that in the comparative example. Matrine is embedded in its annular cavity through β-cyclodextrin to form an ultramicrocapsular inclusion complex. When encountering blood, the affinity of water molecules to the external hydroxyl groups of cyclodextrin is enhanced, resulting in a weakened binding force between matrine and β-cyclodextrin, thereby releasing matrine, and the antibacterial ability does not change significantly before and after water permeation; the water absorption speed and air permeability of Example 1-Example 3 are significantly better than those of the comparative example. The antibacterial composite resin powder is an interpenetrating polymer network with a large pore structure and high water absorption performance, which enhances the antibacterial The strength of the composite resin is improved, and the water absorption and air permeability are improved, and more nano-antibacterial inclusion compounds can be evenly distributed and carried. The released matrine is tightly adsorbed on the surface through van der Waals force to achieve a long-lasting antibacterial effect; the resilience and strength of Examples 1 to 3 are significantly better than those of the comparative example. The composite aerogel sheet prepared using titanium dioxide, bagasse fiber and zeolite as raw materials helps to increase the intermolecular force, has an extremely high specific surface area, a nano-scale pore structure and an extremely low thermal conductivity, can effectively prevent heat transfer, increase air permeability, and help to improve the stuffiness caused by wearing menstrual pants for a long time.
[0068] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing dry antibacterial menstrual pants, characterized in that: The steps include: The hydrophilic nonwoven fabric as the surface layer, the antibacterial sandwich layer, the hot air nonwoven fabric as the guide layer, the absorbent core layer and the PP breathable microporous film as the bottom film are cut and formed respectively, overlapped in sequence, and bonded by hot melt adhesive to obtain the trouser crotch part, and the trouser crotch part and the trouser waist part are bonded by hot melt adhesive to obtain the dry antibacterial menstrual pants; the absorbent core is a mixed material of nonwoven fabric wrapped with fluff pulp and super absorbent resin; The antibacterial sandwich layer is prepared by the following steps: Step 1: adding 50-60wt% of matrine solution to a reactor containing 70-75wt% of β-cyclodextrin solution, ultrasonically dispersing for 40-60min, continuing stirring for 2-3h, adding anhydrous ethanol to the reactor and stirring for 20-30min, cooling and crystallizing at 0-4°C for 8-12h, filtering, washing the filter cake with 30-35% ethanol solution by volume for 2-3 times to remove the residual matrine in the filter cake, and vacuum drying at 60-80°C for 1-2h to obtain a nano antibacterial inclusion compound powder; Step 2: mixing the macroporous super absorbent resin powder and the nano antibacterial inclusion compound powder in a mass ratio of 2:1 to obtain an antibacterial composite resin powder; Step 3: Mix the antibacterial composite resin powder at 0.1-0.2g / cm 2 The spraying amount is evenly sprayed on the surface of the composite aerogel sheet to obtain an antibacterial sandwich layer.
2. The method for preparing a dry antibacterial menstrual pants according to claim 1, characterized in that: The usage ratio of the matrine solution, the β-cyclodextrin solution and the anhydrous ethanol in step 1 is 200-250 mL: 300-350 mL: 300-310 mL.
3. The method for preparing the dry antibacterial menstrual pants according to claim 1, characterized in that: The macroporous super absorbent resin powder in step 2 is prepared by the following steps: Add styrene, divinylbenzene, isooctane, benzoyl peroxide, polyvinyl alcohol and deionized water into a reaction kettle, stir at 60-70°C and 400-500r / min for 20-30min, add absorbent resin powder into the reaction kettle for swelling, continue stirring and reacting for 4-6h, filter by suction, wash the filter cake with deionized water at 80-85°C for 4-5 times, dry under vacuum at 60-80°C to constant weight, crush, and pass through a 180-200 mesh sieve to obtain macroporous super absorbent resin powder.
4. The method for preparing the dry antibacterial menstrual pants according to claim 3, characterized in that: The dosage ratio of styrene, divinylbenzene, isooctane, benzoyl peroxide, polyvinyl alcohol, deionized water and water-absorbing resin powder is 90-100g: 300-350mL: 110-120g: 10-12g: 6-8g: 550-600mL: 200-210g.
5. The method for preparing the dry antibacterial menstrual pants according to claim 1, characterized in that: The composite aerogel sheet in step 3 is prepared by the following steps: Add glacial acetic acid and anhydrous ethanol to a reactor, ultrasonically disperse for 40-60 minutes, stir at 20-25°C and 200-300 r / min for 30-45 minutes, add 70-75wt% tetrabutyl titanate solution, bagasse fiber suspension, nano zeolite and deionized water to the reactor, ultrasonically disperse for 40-60 minutes, stir at 20-25°C and 200-300 r / min for 20-30 minutes, then pour the obtained mixed solution into a mold and freeze it with liquid nitrogen for 10-12 minutes, then place it in a freeze dryer for freeze drying for 48-50 hours, cut and shape to obtain a 1-2 mm composite aerogel sheet; The freeze drying temperature is -96.5°C and the pressure is 13.0-14.0Pa.
6. The method for preparing the dry antibacterial menstrual pants according to claim 3, characterized in that: The water-absorbing resin powder is prepared by the following steps: Add starch and deionized water to a reactor, heat to 90-100° C. under nitrogen protection, gelatinize for 30-40 minutes, cool to 55-65° C., add acrylic acid solution with a neutralization degree of 45-55% and N,N'-methylenebisacrylamide to the reactor, add ammonium sulfate solution at a rate of 30-40 drops / min under nitrogen protection, stir at 60-70° C. and 200-300 r / min for 3-4 hours after the addition is complete, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, dry in vacuum at 60-80° C. for 1-2 hours, crush, and pass through a 100-120 mesh sieve to obtain a water-absorbing resin powder; The concentration of acrylic acid in the acrylic acid solution with a neutralization degree of 45-55% is 5-6 mol / L.
7. The method for preparing the dry antibacterial menstrual pants according to claim 5, characterized in that: The bagasse fiber suspension is prepared by the following steps: After the bagasse is deflated by a pulp defragmenter, it is soaked in deionized water for 12-15 hours and ground at a grinding speed of 1500-1600 r / pm for 5-6 cycles, each cycle lasting 30-40 minutes, to obtain a bagasse fiber suspension with a solid content of 4-5wt%.
8. The method for preparing the dry antibacterial menstrual pants according to claim 5, characterized in that: The usage ratio of the glacial acetic acid, anhydrous ethanol, tetrabutyl titanate solution, bagasse fiber suspension, nano zeolite and ion water in the step is 50-80g: 220-250mL: 50-60mL: 100-120mL: 100-120g: 400-450mL.
9. The method for preparing the dry antibacterial menstrual pants according to claim 6, characterized in that: The usage ratio of the starch, deionized water, acrylic acid solution, N,N'-methylenebisacrylamide and ammonium sulfate solution is 180-200 g: 500-600 mL: 100-120 mL: 120-130 g: 120-130 mL.
10. A dry antibacterial menstrual pants, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Menstrual period trousers
CN113274197A
Cited By
Menstrual period trousers and production process thereof
CN120713702A
Menstrual pants and process for their production
CN120713702B